Analysis of the Finite Element Method in Reinforcing Soft Soil using Geotextiles - Pranadya Krida Palgunadi; Togani Cahyadi U (Jurnal Teknik Sipil dan Perencanaan, 2024)
This study focuses on the analysis of the finite element method for soft soil reinforcement using geotextiles in the Tambak Lorok area, Tanjung Emas Village, Semarang Utara District, Central Java. The research location was selected because this area is experiencing rapid economic and infrastructure development, but faces significant soil subsidence issues due to the high swelling-shrinking potential of clay soil. This subsidence negatively impacts building stability as well as the social and economic lives of the community. This study aims to evaluate the stability of fill soil with and without geotextile reinforcement using Plaxis 2D software. The research method used is quantitative, with analysis using Plaxis 2D to evaluate the stability of the original fill soil with and without geotextile reinforcement. The data used includes secondary data from government agencies and primary data from standard penetration tests (SPT) as well as interviews with local residents. This study is limited to the location on Tambak Mulyo Road, with aspects reviewed including the extent of soil subsidence and the safety factor of the fill. The software used is PLAXIS 2D, and Google Maps historical data and interview results are used for data validation. The analysis results show that the stability level of the original fill soil without geotextile tends to be lower, with significant soil settlement at the measurement point. Before the application of geotextile, the safety factor value of the fill soil was 1.407. After the application of geotextile with a tensile strength of 200 kN/m², the safety factor increased to 1.507. These results indicate that the use of geotextile is effective in enhancing the stability of fill soil in the Tambak Lorok area, North Semarang.